The Concept of a Humanistic Da'wah Approach for Young People: A Qualitative Study on Qur'anic Friendly Communication in the City of Bandung - Samsudin, Ahmad (Sahabat Publikasi, 2026)
This study aims to examine the humanistic da'wah approach employed by the Gemar Qur'an Community in the city of Bandung in targeting young people. Humanistic da'wah emphasizes aspects of humanity, empathy, dialogue, and empowerment, which align with the spiritual and psychological needs of today's young generation. Using a qualitative method with a case study approach, this research conducted in-depth interviews, participatory observations, and document analysis to explore the strategies and impacts of humanistic da'wah applied in the Gemar Qur'an Community. The results indicate that the Gemar Qur'an Community has succeeded in creating an inclusive and transformative da'wah space by utilizing social media, Qur'anic mentoring, and a participatory emotional approach. This has positively impacted changes in religious behavior, increased interest in the Qur'an, and the formation of a spiritually strengthening community. This study recommends the replication of the humanistic approach in da'wah targeting young people across various other communities, as well as the need for synergy with educational and religious institutions.